Supercell-enhanced multimodal plasmonic sensor for high-fidelity antigen detection via refractive index modulation - MohammadAli Shokrzadeh Moghtader; Hamid Heidarzadeh; Ali Khodaie (Scientific Reports)
Abstract In this study, we investigate a multispectral plasmonic refractive index sensor based on a ring resonator supercell array for the detection of carcinoembryonic antigen (CEA), prostate-specific antigen (PSA), and hemoglobin (Hb). The sensor exhibits three resonance modes within the 1000–3000 nm wavelength range, analyzed using the finite-difference time-domain (FDTD) method. Through meticulous optimization of the sensor’s geometrical structure, we achieve a high figure of merit (FOM) and sensitivity. Notably, the second resonance mode attains the highest sensitivity of 913.51 nm/RIU. Furthermore, the third resonance mode achieves an FOM exceeding 70 RIU−1, underscoring its potential for specialized biomedical applications. Extensive research has established a strong correlation between elevated antigen concentrations, including CEA, PSA, and hemoglobin, and the presence of cancer and other critical diseases. With advancements in optical biosensing technology, this sensor offers a promising pathway toward cost-effective, portable, and highly sensitive diagnostic tools, contributing to public health and improved quality of life.